2022
DOI: 10.3389/fonc.2022.864132
|View full text |Cite
|
Sign up to set email alerts
|

Cause of Death During Renal Cell Carcinoma Survivorship: A Contemporary, Population-Based Analysis

Abstract: BackgroundAs the survival rates of patients with renal cell carcinoma (RCC) continue to increase, noncancer causes of death cannot be ignored. The cause-specific mortality in patients with RCC is not well understood.ObjectiveOur study aimed to explore the mortality patterns of contemporary RCC survivors.MethodsWe performed a retrospective cohort study involving patients with RCC from the Surveillance, Epidemiology, and End Results (SEER) database. We used standardized mortality ratios (SMRs) to compare the dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Multiple studies found that patients with genitourinary cancers were at a generally increased risk of suicide. However, this risk increase varied based on the exact type of cancer, cancer severity, and the treatments received [13][14][15][16]. A 2015 paper by Klaassen, et al used SEER data from 1988 to 2010 and found that, as compared with the age-matched US population, patients with bladder (SMR-2.71, 95% CI: 2.02-3.62) and kidney cancer (SMR = 1.86, 95% CI: 1.32-2.62) were at a high risk of suicide, patients with prostate cancer had the highest risk of suicide with increasing time from diagnosis (SMR = 1.84, 95% CI: 1.39-2.41), and patients with bladder cancer had the highest risk of suicide within the first 5 years after diagnosis (SMR = 3.05, 95% CI: 2.26-3.96) [16].…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies found that patients with genitourinary cancers were at a generally increased risk of suicide. However, this risk increase varied based on the exact type of cancer, cancer severity, and the treatments received [13][14][15][16]. A 2015 paper by Klaassen, et al used SEER data from 1988 to 2010 and found that, as compared with the age-matched US population, patients with bladder (SMR-2.71, 95% CI: 2.02-3.62) and kidney cancer (SMR = 1.86, 95% CI: 1.32-2.62) were at a high risk of suicide, patients with prostate cancer had the highest risk of suicide with increasing time from diagnosis (SMR = 1.84, 95% CI: 1.39-2.41), and patients with bladder cancer had the highest risk of suicide within the first 5 years after diagnosis (SMR = 3.05, 95% CI: 2.26-3.96) [16].…”
Section: Search Resultsmentioning
confidence: 99%
“…A 2016 paper by Klaassen, et al that examined SEER data from 1988 to 2010 also found that among patients with bladder cancer, radical cystectomy further increased patients' suicide risk as compared to the general population (SMR = 3.54, 95% CI: 2.70-4.54) [13]. A 2022 paper by Yu, et al examined SEER data from 2004 to 2015 and found that among patients with renal cell carcinoma, patients at most stages did not have an elevated risk of suicide, but patients with stage IV cancer had a significantly elevated risk of suicide as compared to the general population (SMR = 2.24, 95% CI: 2.11-2.38) [15].…”
Section: Search Resultsmentioning
confidence: 99%
“…Compared with married patients, unmarried GBC patients has higher risk of non cancer death, confirming previous reports 39 , 42 . The fact that marriage provides social support may explain this finding 30 . GBC patients diagnosed between 2010 and 2017 has lower risk of non cancer death than diagnosed between 2004 and 2009, possibly due to the advances in medical technology and growing emphasis on death from non cancer causes 43 .…”
Section: Discussionmentioning
confidence: 96%
“…The development of sepsis is often associated with cancer related treatments, both surgery and chemotherapy increase the risk of sepsis 26,27 . In addition, neutropenia as a result of antitumor therapy is a common clinical phenomenon, which has been shown to be independently associated with sepsis [28][29][30] . Compared with general population, cancer patients has greater risk of death from pneumonia 31 , our research get the similar conclusion in GBC patients (SMR, 1.50; 95%CI, 1.03-2.12).…”
Section: Discussionmentioning
confidence: 99%